Intimate integration: A study of aboriginal transracial adoption in Saskatchewan, 1944-1984 - Stevenson, Allyson (2015)
The term intimacy brings to mind a type of familiarity between people that surpasses mere affection. Intimacy suggests a deeply personal relationship based on shared experiences, love, and the pursuit of common goals. The intimate lives of families, shared in the domestic sphere, are often thought to be beyond the reach of the state. By contrast, this dissertation demonstrates that intimacy has been the focus of the state through Indian Act legislation and child welfare programs that have uniquely intersected through the lives of First Nations and Métis women and children. Aboriginal transracial adoption provides a particularly vivid example of state sanctioned intimacy. Programs such as the Adopt Indian and Métis program, later known as AIM, REACH and the American version, the Indian Adoption Program, (IAP), created intimate bonds between white families and Aboriginal children. Transracial adoption represents a revolution in integration. The period of integration that took shape after the Second World War manifested in increased interventions of social welfare workers who encountered Aboriginal women and children in various domains. Race, gender, and space are interrogated through exploring Aboriginal women’s responses to the opportunities provided by increased access to child welfare programs, as well the limitations and serious handicaps that came as a consequence of their particular gendered and racialized location. In Saskatchewan, the CCF government under the direction of Tommy Douglas sought to utilize “technologies of helping”, a secular therapeutic social welfare approach to the problem of Métis marginalization and poverty through the Department of Social Welfare and Rehabilitation to effect Métis integration. Initially envisioned as series of government supported colonies to which Métis were relocated, the Métis policy eventually evolved to focus primarily on Métis children, and tangentially on Métis women. The Adopt Indian and Métis program, coming on the heels of failed relocation policies, ...